2021
DOI: 10.1371/journal.pone.0251938
|View full text |Cite
|
Sign up to set email alerts
|

Suicide along the Australian coast: Exploring the epidemiology and risk factors

Abstract: Suicide is an increasing global concern with multiple risk factors, yet location-based understanding is limited. In Australia, surf lifesavers (SLS) and lifeguards patrol the coast, performing rescues and assisting injured people, including people who suicide. This study is a descriptive epidemiological analysis of Australian coastal suicide deaths. The results will be used to inform training and support surf lifesaving personnel and suicide prevention organisations. This is a population-based cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
0
8
1
Order By: Relevance
“… 27 In addition to diagnosed depression, 18/81 (22%) of those who died by suicide in our study had a severe mental illness, based on the reported diagnosis, the medications prescribed and the history of recent hospital admission. Comorbid substance misuse was known to be present in 38% of deaths by suicide in the systematic review of psychological autopsies 27 and in a similar proportion in a large Australian study that also used NCIS data; 28 this is a little higher than the diagnoses of substance use disorder recorded in our study, although 41.6% of the present sample had alcohol present and 20.8% had illegal drugs present at the time of death. The results suggests that substance use, particularly the use of substances likely to exacerbate low mood, reduce inhibition and increase the tendency to act on impulse (such as alcohol and amphetamine), is a significant risk factor for suicide.…”
Section: Discussioncontrasting
confidence: 41%
“… 27 In addition to diagnosed depression, 18/81 (22%) of those who died by suicide in our study had a severe mental illness, based on the reported diagnosis, the medications prescribed and the history of recent hospital admission. Comorbid substance misuse was known to be present in 38% of deaths by suicide in the systematic review of psychological autopsies 27 and in a similar proportion in a large Australian study that also used NCIS data; 28 this is a little higher than the diagnoses of substance use disorder recorded in our study, although 41.6% of the present sample had alcohol present and 20.8% had illegal drugs present at the time of death. The results suggests that substance use, particularly the use of substances likely to exacerbate low mood, reduce inhibition and increase the tendency to act on impulse (such as alcohol and amphetamine), is a significant risk factor for suicide.…”
Section: Discussioncontrasting
confidence: 41%
“…With respect to grouped medical conditions, diseases of the nervous system [ 7 , 11 , 19 , 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and mental and behavioural conditions [ 7 , 37 , 42 , 43 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 17 studies that discussed 26 unique strategies for preventing drowning related to pre-existing medical conditions [ 7 , 11 , 19 , 31 , 34 , 41 , 44 , 47 , 48 , 53 , 57 , 59 , 68 , 77 , 89 , 91 , 96 ]. The majority of strategies were administrative in nature when aligned to the Hierarchy of Control (n = 24; 92.3%) and all were proposed, as opposed to implemented and/or evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…153-162). On the other hand, in Australia, researcher found that the number of suicides increased in a week before and a week after public holidays (J.C. Lawes et al [26]). Research in Japan over 1979-1994 showed that the rate of suicides was the lowest on the days before a holiday and the highest on the days after a holiday (M. Nishi et al [27], pp.…”
Section: Introductionmentioning
confidence: 99%